Analysis on Black Shale Sedimentary Paleoenvironment and Tectonic Setting of the First Member of Luzhai Formation of Lower Carboniferous, Rongshui Area of Guangxi, China - Juan Li; Yinglun Qin; Huanpeng Chi; Yukun Tian; Yufang Wang; Liyun Kong (Geofluids)
In order to promote the discovery of new shale gas exploration areas in Guangxi, based on the latest drilling data, through detailed observation and description of logging data and cores, this paper selects high-quality shale samples of the target layer for X-ray diffraction analysis and testing of clay minerals and whole rock, major and trace elements (including rare-earth elements), TOC, and other related analysis and testing. The study shows that the total amount of rare-earth elements in the first member of Lower Carboniferous Luzhai Formation in Rongshui area, Guangxi, is low; δEU and δCE show negative abnormality. The average value of wV/V+Ni, Th / U ratio, and Mo-TOC covariant model diagram of the first member of Luzhai Formation show that it was the condition of anoxic reduction at that time. At the same time, Ba-Sr diagram, Sr/Cu ratio, and total rare-earth elements reflect that the area was in an arid, hot, and marine salt water paleoenvironment during the sedimentary period. Most of the sample parent rocks of the first member of Luzhai Formation are in shale area, and some samples are close to felsic igneous rock area, which is of mixed origin. The tectonic background of the source area is mainly continental island arc and active continental margin, indicating that the sedimentary environment was unstable and highly active under the background of extensional rifting at that time.